Model egzegezy w dziele Josepha Ratzingera – Benedykta XVI Jezus z Nazaretu cz. 1. - Pieczyńska, Anna (Collectanea Theologica, 2019)
This article presents the method of Bible interpretation which was chosen by Benedict XVI in his book Jesus of Nazareth pt. l. Using this method, Joseph Ratzinger was looking for an answer to the question about the true identity of Jesus Christ. In this article, the author makes an attempt to present examples of the Pope’s use of various exegetical methods. This helps us to understand Benedict’s opinion which in his book is clearly stated, namely there is no single correct method of Bible interpretation which gives us definitive answer. Frequent references to the canonical method result from the fact that for Benedict XVI faith remains a priority for in the interpretation of the Holy Scriptures in the Catholic Church. Skillfully drawing from the treasury of Tradition and contemporary development of knowledge, the Pope engaged substantially in polemics with these interpretative tendencies, which in his opinion do not lead to the discovery of biblical truths.